Шляхи вдосконалення діяльності органів державної влади в умовах воєнного стану - Моргунов, О. А.; Morgunov, O. A.; Музичук, О. М.; Muzychuk, O. M. (Південноукраїнський правничий часопис. - 2023. - № 2. - С. 104-108, 2023)
Визначено перспективні шляхи вдосконалення діяльності органів державної влади в Україні через призму їх сутнісного аналізу в умовах воєнного стану. Розглянуто позиції науковців стосовно вказаної проблематики. Сформовано сутнісне розуміння категорії «органи державної влади» в умовах воєнного стану та визначено їх особливості, характерні принципи діяльності у досліджуваний період. Запропоновано шляхи вдосконалення діяльності органів державної влади в умовах воєнного стану.

Based on the analysis of the scientific views of scientists and the study of the activities of state authorities in Ukraine, the peculiarities of the activities of state authorities in conditions of martial law are highlighted, namely, an adaptive approach to the formation of the staff of a certain state authority, including the use of shift methods, the possibility of remote work regime; expansion of the competence of state authorities due to the performance of tasks and functions that were not previously inherent to them, especially in the regions of active hostilities; rethinking the territory of action of executive authorities with the possibility of redeployment to other territories in the actual execution of the powers entrusted to them; the growth of the role of interaction of various state authorities within the state apparatus for the mutual overlap of certain functions in the conditions of martial law. On the basis of the above features, the latest principles of the activity of state authorities were formed, which are characteristic of the martial law regime, including the principles of complementarity and adaptability. On the basis of the established provisions and approaches, the ways of improving the activities of state authorities in the conditions of martial law are identified, in particular, the implementation of the principle of adaptability in the activities of state authorities at the level of rule-making and management decisions; expansion of the list of virtual resources, sites, pages in social networks, platforms, channels that can be used for remote communication with the population; organizational and regulatory regulation of the widest possible range of processes within the framework of the interaction of various state authorities within the state apparatus to ensure their complementarity; careful planning of the activities of state authorities; increasing the social status of the civil service, the salaries of civil servants of the lower and middle ranks in the conditions of increasing the level of trust of the population in state institutions in order to prevent corruption.

Определены перспективные пути усовершенствования деятельности органов государственной власти в Украине через призму их сущностного анализа в условиях военного положения. Рассмотрены позиции ученых по данной проблематике. Сформировано сущностное понимание категории "органы государственной власти" в условиях военного положения и определены их особенности, характерные принципы деятельности в исследуемый период. Предложены пути усовершенствования деятельности органов государственной власти в условиях военного положения.
Ways of improving the activity of state authorities in the conditions of martial law
Keywords: органи державної влади; державний апарат; воєнний стан; взаємодія; публічне адміністрування; ефективність; вдосконалення; state authorities; state apparatus; martial law; interaction; public administration; efficiency; improvement; органы государственной власти; государственный аппарат; военное положение; взаимодействие; публичное администрирование; эффективность; усовершенствование